Socio-emotional Wealth Dimensions Defining the Corporate Social Responsibility Competencies of Family Businesses in the Philippines - Eunice Mareth Querol Areola, PhD HSG (Journal of Sustainable Community Development (JSCD), 2023)
As concern about society and the environment grows, pressure about sustainability rises. Businesses take action in engaging Corporate Social Responsibility (CSR) in its organizational objectives. The dominance of family business in the business society signifies its importance and contribution to the growth of sustainability. In the Philippines, CSR remains to be poorly developed and references about family businesses are inadequate. This research aims to examine the degree of Socio-emotional Wealth (SEW) and CSR practices of family businesses and to assess the relationship of these two variables in order to establish findings that would help improve family businesses and their CSR practices. The results showed that Scio-emotional wealth or SEW dimensions and CSR practices are significantly correlated. Conclusions were established and recommendations were formulated. In general, the recommendations of this research are for preservation and strengthening of family businesses’ SEW dimensions for the improvement of the businesses’ CSR engagements.